Leadership and Administrative Practices in Supervising Work-Based Learning: Performance Outcomes of TVET Tourism Students in the Tourism Industry (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigated the supervised work-based learning (SWBL) performance of Technical-Vocational Education and Training (TVET) tourism students deployed in partner tourism establishments in Digos City, Philippines, during Academic Year 2022–2023. Employing a descriptive-comparative quantitative research design, the study assessed students’ performance across basic, common, and core competencies as defined by the Technical Education and Skills Development Authority (TESDA). A structured questionnaire using a five-point Likert scale was administered to industry trainers who directly supervised the trainees. Descriptive statistics and analysis of variance (ANOVA) were used to analyze the data.